2011
DOI: 10.1097/brs.0b013e31820611ba
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluations of Various C1-C2 Posterior Fixation Techniques

Abstract: The TAS 1 MG procedures provided the highest stability. The MG method alone may not be adequate for atlantoaxial arthrodesis, because it does not provide sufficient stability in lateral bending and rotation modes. The C2 pedicle screw and C2 ILS techniques are biomechanically less stable than the TAS 1 MG. In the C1 lateral mass-C2 pedicle screw fixation, the use of a short pedicle screw may be an alternative when other screw fixation techniques are not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 23 publications
4
68
0
7
Order By: Relevance
“…Sim et al 40 reported that the C1-C2TA construct provided better biomechanical stabilization than the C1LM-C2PS construct in flexion/extension only, whereas Guo et al 15 reported better stabilization in axial rotation only. Li et al, 28 Hott et al, 19 and Ma et al 29 did not find significant differences in the stabilization achieved with the C1-C2TA and C1LM-C2PS constructs in any degree of motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sim et al 40 reported that the C1-C2TA construct provided better biomechanical stabilization than the C1LM-C2PS construct in flexion/extension only, whereas Guo et al 15 reported better stabilization in axial rotation only. Li et al, 28 Hott et al, 19 and Ma et al 29 did not find significant differences in the stabilization achieved with the C1-C2TA and C1LM-C2PS constructs in any degree of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis was performed for C1-2 transarticular screw (C1-C2TA [n = 5]), 15,19,25,29,38,39 C1 lateral mass-C2 pedicle screw (C1LM-C2PS [n = 10]), 7,15,19,25,27,29,34,37,40 C1LM-C2TL (n = 3), 7,27,40 and C1LM-C2 pars (n = 3) constructs. 7,23 Anterior-approach transarticular screw and C1 lateral mass-C3 lateral mass screw constructs were excluded from the meta-analysis because each technique was reported only once in the included articles.…”
Section: Screw Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though technically more challenged, requiring a CT angiogram study before its use to visualize the vertebral artery course in the C1-2 region, biomechanical studies suggest that this construction provides the highest level of stability in this region 22 .…”
mentioning
confidence: 99%
“…Although we do not use this technique for axis fixation in any case in this series because of surgeon's personal preference (AFJ) in using C1 lateral mass screws, C1-2 transarticular screw fixation to stabilize C1 and C2 is widely used and described in literature 22 . Even though technically more challenged, requiring a CT angiogram study before its use to visualize the vertebral artery course in the C1-2 region, biomechanical studies suggest that this construction provides the highest level of stability in this region 22 .…”
mentioning
confidence: 99%